Overcoming the voltage losses caused by the acceptor‐based interlayer in laminated indoor OPVs - Gulzada Beket; Anton Zubayer; Qilun Zhang; Jochen Stahn; Fredrik Eriksson; Mats Fahlman; Thomas Österberg; Jonas Bergqvist; Feng Gao (SmartMat, 2024)
Abstract Harvesting indoor light to power electronic devices for the Internet of Things has become an application scenario for emerging photovoltaics, especially utilizing organic photovoltaics (OPVs). Combined liquid‐ and solid‐state processing, such as printing and lamination used in industry for developing indoor OPVs, also provides a new opportunity to investigate the device structure, which is otherwise hardly possible based on the conventional approach due to solvent orthogonality. This study investigates the impact of fullerene‐based acceptor interlayer on the performance of conjugated polymer–fullerene‐based laminated OPVs for indoor applications. We observe open‐circuit voltage (VOC) loss across the interface despite this arrangement being presumed to be ideal for optimal device performance. Incorporating insulating organic components such as polyethyleneimine (PEI) or polystyrene (PS) into fullerene interlayers decreases the work function of the cathode, leading to better energy level alignment with the active layer (AL) and reducing the VOC loss across the interface. Neutron reflectivity studies further uncover two different mechanisms behind the VOC increase upon the incorporation of these insulating organic components. The self‐organized PEI layer could hinder the transfer of holes from the AL to the acceptor interlayer, while the gradient distribution of the PS‐incorporated fullerene interlayer eliminates the thermalization losses. This work highlights the importance of structural dynamics near the extraction interfaces in OPVs and provides experimental demonstrations of interface investigation between solution‐processed cathodic fullerene layer and bulk heterojunction AL.